Radiation-induced dermatitis after administration of mogamulizumab for adult T-cell leukaemia/lymphoma: a multi-institutional retrospective study. (17th November 2018) - Maemoto, Hitoshi; Ariga, Takuro; Kusada, Takeaki; Heianna, Joichi; Manabe, Yoshihiko; Miyakawa, Akifumi; Nakachi, Sawako; Morishima, Satoko; Iraha, Shiro; Ganaha, Fumikiyo; Masuzaki, Hiroaki; Murayama, Sadayuki
Abstract : None of the 15 patients with adult T-cell leukaemia/lymphoma developed Grade ≥3 radiation-induced dermatitis during a total of 46 courses of moderate-dose radiotherapy after the administration of mogamulizumab. Abstract: Background: Cutaneous adverse reactions are frequently induced by mogamulizumab. Cases of Stevens–Johnson syndrome, toxic epidermal necrolysis and severe photosensitivity related to mogamulizumab have been reported. This study investigated whether severe radiation-induced dermatitis occurred in patients undergoing radiotherapy after the administration of mogamulizumab for adult T-cell leukaemia/lymphoma. Methods: We retrospectively reviewed 46 courses of radiotherapy administered to 15 consecutive patients with adult T-cell leukaemia/lymphoma (acute, n = 7; lymphoma, n = 7; smouldering, n = 1) who received mogamulizumab before or during radiotherapy at three institutions between 2012 and 2017. Results: During 43 of the 46 radiotherapy courses, patients developed Grade ≤1 radiation-induced dermatitis. No patient developed Grade ≥3 radiation-induced dermatitis. No patient was prescribed ointments as prophylactic treatment for radiation-induced dermatitis. Development of radiation-induced dermatitis was not significantly associated with the number of days since the administration of mogamulizumab prior to radiotherapy ( P = 0.85), frequency of administration of mogamulizumab before/during radiotherapy ( P = 0.33), administration of mogamulizumab during radiotherapy ( P = 0.41) or types of lesions in adult T-cell leukaemia/lymphoma cases (cutaneous vs. non-cutaneous, P = 0.74). Development of radiation-induced dermatitis was significantly related to the total cutaneous dose (mean, 31.9 Gy [95% confidence interval: 26.6–37.1 Gy] vs. 19.7 Gy [95% confidence interval: 16.2–23.2 Gy], P = 0.0004) and total prescribed dose (mean, 31.5 Gy [95% confidence interval: 26.2–36.8 Gy] vs. 18.5 Gy [95% confidence interval: 15.0–22.0 Gy], P = 0.0002). Conclusion: None of the 15 patients who received moderate-dose radiotherapy developed severe radiation-induced dermatitis during the 46 courses of radiotherapy after mogamulizumab administration.